Frecuencia de síndrome metabólico en la población indígena adulta de 40 a 60 años de los barrios Ilincho y las Lagunas del cantón Saraguro en el periodo abril a septiembre del 2012. - Paqui Quizhpe, Gloria Esperanza (2013)
The International Diabetes Federation (IDF) called Metabolic Syndrome (MS) to the set of metabolic alterations consist centrally distributed obesity, decreased HDL cholesterol, elevated triglyceride levels, increased blood pressure and hyperglycemia . The diagnosis is verifiable through testing and analysis that may be practiced in any medical facility for it is economical and reliable. The objective of this research work is to determine the frequency of MS in the adult Indian population 40-60 years Ilincho neighborhoods and Las Lagunas of Saraguro Canton, will focus on age group, gender and establish if dietary habits and physical activity affecting it. The type of study is a prospective, descriptive, cross-sectional, the data were collected through a survey conducted by the author, persons presenting abdominal circumference greater than set according to IDF also recorded age, gender, dietary habits, physical activity and blood pressure, then blood tests conducted to determine the other criteria and obtain the frequency of metabolic syndrome. The sample consisted of 62 people of which 60% are female and 40% male, the total, 30% are aged between 56-60 years, in terms of risk factors, 32% have impaired triglycerides , 27% to impaired fasting glucose and 11% have impaired blood pressure and in final form, 29% had 3 or more criteria for metabolic syndrome co, in addition it was found that power is based on carbohydrates and fats, whereas physical activity by more than 30 minutes more than 70% is carried out only once a week. KEYWORDS: Metabolic syndrome, indigenous population, diet, physical activity.